O vínculo mãe bebê: primeiros contatos e a importância do holding - Pommé, Eliana Lemos (2008)
This study focus the binding behaviors between mother and baby in puerperal women, who has delivered her babies in the Labor Center of Amparo Maternal, in the city of São Paulo. His main goal is to describe the manifestations of binding behavior between mother and baby in the first time they're together after the labor and to analyse the function of holding in promoting this bind. The term holding is used as a context of caring and support the mother gives to her newborn baby, as well as the mother's family gives to herself. The psychoanalytical concepts about the puerperal-pregnant cycle(Winnicot,Maldonado,Szejer),the baby's contemporary theorists(Stern, Lichtenberg) and the body-mind approach of Wilhelm Reich in the prevention of health are the theoretical basis of this study. The data was obtained through video recording the mother-baby relationship and through semi directed clinic interviews with the puerperals.From the results, two different groups of mothers aroused, in respect to the holding, in two situations : From the interaction mother-baby, and from the interaction of the mother with her family. The study points out to the very important function of the family holding throughout pregnancy and how having holding after the labor promotes the binding between mother and the baby. This study contributes to the comprehension of the psychological assistance as a path to promote the biding, therefore widing the universe of interference in the pregnant-puerperal cycle to the families